Hubungan Durasi Mengemudi Dengan Keluhan Nyeri Punggung Bawah (Low Back Pain) Pada Pengemudi Bus Akap Di Terminal Kampung Rambutan Tahun 2023 - Parnonto, Wiratama Ibnu; Djaali, Nur Asniati; Endarti, Ajeng Tias (Jurnal Ilmiah Kesehatan, 2024)
Background: Low back pain disease varies greatly every year with a figure of 15-45%. According to the WHO, 33% of the population in developing countries experience persistent pain. Work as a bus driver is prone to low back pain, resulting from the factors of sitting for a long time in conditions of static vibration, vibration due to the road, ergonomic factors, and the type of seat on the vehicle will cause rapid fatigue and soreness in the waist/lower back area. Objective: to determine the relationship between driving duration and complaints of low back pain in AKAP Bus Drivers at Kampung Rambutan Terminal in 2023 Method: the study used an analytical survey with a cross sectional research design. This research was carried out at the Kampung Rambutan Terminal in July 2023. A sample of 198 respondents was taken using simple randong sampling. The implementation of this research was carried out by distributing questionnaires to respondents. Results: 76 respondents (38.4%) experienced complaints of low back pain and 122 respondents (61.6%) did not experience complaints of low back pain, 167 respondents (84.3%) and 31 respondents (15.7%) had normal driving duration. There is a relationship between driving duration and complaints of low back pain in AKAP Bus Drivers at the Kampung Rambutan Terminal in 2023 (p value =0.000). Recommendation: It is hoped that the government should be able to conduct regular evaluations of occupational health and safety, especially for bus drivers. Keywords: Lower Back Pain, Driving Duration